Degradasi Senyawa Alizarin-S Secara Sonolysis dan Fotolisis dengan Penambahan TiO2-Anatase - Zuki, Zamzibar; Sakai, Tadao (Jurnal Pilar Sains, 2008)
Degradation of alizarin S dye by added TiO2-anatase had been done by Sonolysis and Photolysis. Sonolysismethod used ultrasonic radiation with frequency on 47 kHz. Degradation of 20 mg/L Alizarin S by addedTiO2-anatase 0,1000 g, optimum pH 5.0, temperature 50± 1 °C and percentage of degradation has reached for100 % after sonolizing for 30 minutes. Photolysis method used UV light irradiation with wavelength is 359nm. Degradation of 20 mg/L alizarin S as photolysis by added TiO2-anatase 0,1000 g, optimum pH 5.0.Percentage of degradation has reached for 100 % after irradiating for 30 minutes.Keywords: Alizarin-S, Sonolisis, Photolysis